Anticipation dialogs in Vermont’s system of mental healthcare: Sustaining the growth of a dialogic practice culture - Alpern, Zelda; Binshadler, Sarah; Oakley, Ashley (Frontiers in Psychology, 2023)
Open dialogue is both a therapeutic approach and a way of organizing the system of care innovated in Finland. In Vermont, over the last decade there has been an organic statewide effort to begin to integrate dialogic principles into the system of care. In our study, we offered anticipation dialogues at three dialogically informed community mental health centers and one public psychiatric hospital to better understand practitioners’ and one service recipient’s visions for the future and what barriers there were to realizing these visions. The anticipation dialogue was developed in Finland during the late 1980s, in which stuck professional and social networks find ways to move forward looking back from an imagined positive future. Twenty-seven multidisciplinary staff members and one service recipient participated in the dialogues. Findings underscore dilemmas entailed in growing a dialogic practice system, including the toll systemic uncertainty takes on workers in the system, as well as the need to offer some open-endedness to the system change process in the spirit of inclusiveness, mutual trust, democracy and reducing hierarchy. Other key findings influencing sustainability of dialogic practices in community mental health include issues of pay, workload and integrating dialogic work into roles rather than adding them to existing responsibilities. Our experiences indicate that Anticipation Dialogues may be a way of conducting systemic research that contributes to the forward momentum of system innovation.